(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The work of high-rise buildings with different piles arrangement foundations is investigated rationally and on a regular grid. The comparative analysis of the results is presented. Typical zones of foundation such as central, lateral, and angular ones are separated. The redistribution of efforts between piles and a grillage is shown. The interaction of piles with different lengths and the grillage in the foundations of high-rise buildings is considered. The numerical modeling of the «base – foundation – superstructure» system is performed. A finite-element model of high-rise buildings comples and a multilayer soil mass is developed. The choice of soil parameters for the deformation model of soil environment on the basis of their identification is shown. Comparative results of calculations with data of field observations on bearing structures behaviour. The features of buildings complex base deformation are revealed.